Avian tuberculosis in a Lady Amherst’s pheasant Chrysolophus amherstiae - Álvarez, Pedro P.; Moroni, Manuel; Verdugo, Claudio (Austral Journal of Veterinary Sciences, 2017)
We report a case of a Lady Amherst’s pheasant (Chrysolophus amherstiae) with diffuse granulomatous lesions in liver, spleen and intestine. Using histopathological and molecular diagnosis we detected Mycobacterium avium subsp. avium, etiological agent of avian tuberculosis. Further studies are needed to understand the role of wild birds in the persistence and transmission of this pathogen.